2021
DOI: 10.12998/wjcc.v9.i6.1329
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of afatinib in a patient with rare EGFR (G724S/R776H) mutations and amplification in lung adenocarcinoma: A case report

Abstract: BACKGROUND The most common EGFR mutations are in-frame deletions in exon 19 and point mutations in exon 21. Cases with classical EGFR mutations show a good response to EGFR tyrosine kinase inhibitors (TKIs), the standard first-line treatment. With the development of next generation sequencing, some uncommon genomic mutations have been detected. However, the effect of TKIs on such uncommon EGFR mutations remains unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…A previous case report of a patients with a G724S mutation showed a remarkable response to the combination of afatinib and osimertinib in 2017; however, tumor progressed rapidly in less than 3 months [1]. In the last half year, there have been several clinical cases that reported that afatinib was effective to G724S mutation [2–5], which is consistent with our results. In this manuscript, under the guidance of molecular docking results, we presented a patient with acquired Exon 19 Deletion(Ex19Del)/G724S mutation who was treated with afatinib and obtained long‐term clinical benefit of more than 20 months till now.…”
Section: Introductionsupporting
confidence: 91%
“…A previous case report of a patients with a G724S mutation showed a remarkable response to the combination of afatinib and osimertinib in 2017; however, tumor progressed rapidly in less than 3 months [1]. In the last half year, there have been several clinical cases that reported that afatinib was effective to G724S mutation [2–5], which is consistent with our results. In this manuscript, under the guidance of molecular docking results, we presented a patient with acquired Exon 19 Deletion(Ex19Del)/G724S mutation who was treated with afatinib and obtained long‐term clinical benefit of more than 20 months till now.…”
Section: Introductionsupporting
confidence: 91%
“…Patients with EGFR E709A/L858R, S720F/G719A, L747P, R776H/L858R, and L833V/H835L mutations also showed a TTF of more than 1 year, which was similar to the previous recommendations and increased our confidence to apply afatinib to these patients. 29,30,33 Presently, the mechanism of drug resistance of TKIs has also been widely concerned. For exon 19 deletions and exon 21 L858R mutations, the acquired EGFR T790M mutation is the primary resistance mechanism to first-and secondgeneration EGFR TKIs, followed by the acquisition of the second drive mutation; the emergence of new clones and the replacement of previously predominant clones; and the activation of some downstream pathways and histological transformations.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with EGFR E709A/L858R, S720F/G719A, L747P, R776H/L858R, and L833V/H835L mutations also showed a TTF of more than 1 year, which was similar to the previous recommendations and increased our confidence to apply afatinib to these patients. 29 , 30 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] 43 Female 19-Del + T790M Chemotherapy PD He et al . [ 37 ] 64 Female G724S + R776H Afatinib GR Bao et al . [ 38 ] 36 Male R670W + H835L + L833V Afatinib + osimertinib GR Yang et al .…”
Section: Discussionmentioning
confidence: 99%